Precision Medicine Approaches to Overcome Resistance to Therapy in Head and Neck Cancers - Ortiz-Cuaran, Sandra; Bouaoud, Jebrane; Karabajakian, Andy; Fayette, Jérôme; Saintigny, Pierre (Frontiers in Oncology, 2021)
Head and Neck Squamous Cell Carcinoma (HNSCC) is the sixth most incident cancer worldwide. More than half of HNSCC patients experience locoregional or distant relapse to treatment, despite aggressive multimodal therapeutic approaches that include surgical resection, radiation therapy and adjuvant chemotherapy. Before the arrival of immunotherapy, systemic chemotherapy was previously employed as the standard first-line protocol with an association of cisplatin or carboplatin plus 5-fluorouracil plus cetuximab (anti-EFGR antibody). Unfortunately, acquisition of therapy resistance is common in patients with HNSCC, and often results in local and distant failure. Despite our better understanding of HNSCC biology, no other molecular targeted agent has been approved for HNSCC. In this review, we outline the mechanisms of resistance to the therapeutic strategies currently used in HNSCC, discuss combination treatment strategies to overcome them and summarize the therapeutic regimens that are presently being evaluated in early and late-phase clinical trials.